Exploring the Dark Green. Three Petrotexts by Primo Levi (ENTHYMEMA, 2023)
This paper discusses three science fiction short stories by Primo Levi as petrotexts: “Cladonia rapida” (Storie naturali, 1966), “Ottima è l’acqua” (Vizio di forma, 1971), and “I gladiatori” (Lilit e altri racconti, 1981). Specifically, the first two stories concern the diffusion of automobiles in Italy, while the other is about pollution. While these stories do not address explicitly environmental concerns, I argue that they use science fiction to describe the dramatic environmental changes caused in Italy by the economic boom. The many aspects and contradictions of Levi’s representation of oil are framed within the critical tools of petroculture and the ‘dark green’ theorized by Heather I. Sullivan.
Keywords: Primo Levi; Science Fiction; Environmental Humanities; Ecocriticism; Oil